2017
DOI: 10.5430/jnep.v8n2p56
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of an educational intervention to improve nurses’ knowledge of blood pressure measurement

Abstract: Background: Accurate blood pressure (BP) measurement is a constant challenge, particularly in intensive care units. Thus, studies focusing on avoiding errors in practices of measuring BP are important to patient safety. The objective was to assess the effects of an educational intervention addressing BP measurement, targeting the theoretical and practical knowledge of nurses from a cardiac unit. Methods: This quasi-experimental, before-and-after, study was conducted in a large tertiary hospital in Brazil and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 20 publications
(27 reference statements)
0
7
0
Order By: Relevance
“…This inadequate knowledge level has been reported in other studies as well. The studies by Machado et al, [ 23 ] and Du. [ 25 ], have reported a moderate level of all BPM domains.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This inadequate knowledge level has been reported in other studies as well. The studies by Machado et al, [ 23 ] and Du. [ 25 ], have reported a moderate level of all BPM domains.…”
Section: Discussionmentioning
confidence: 99%
“…This inadequate performance level is found in other studies as well. A study by Machado et al, [ 23 ] has reported a moderate level of all BPM domains among nurses. Another study by Machado et al, [ 30 ] has reported that only 65% of BPM steps were followed by nurses.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations